2021
DOI: 10.1177/09673911211027129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber hybridization on mechanical, thermal, and water absorption behavior of HF/CF/HDPE composites

Abstract: The composite materials are present in nature since the prehistoric era. Applications of fiber-based composite materials are increasing day by day in our society to overcome the raised environmental and economic concerns. Hence, waste fiber can be utilized as the best resource to develop composites. The present study deals with the impact of hybridization on the mechanical, thermal, and water absorption behavior of hair and coir fiber-based hybrid composites. The compression molding technique was used to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…[ 55 ]. Apart from the difference in intensity of the peaks, some authors have reported a modification of the position of the main planes of BioHDPE when different substances are added to the polymer matrix [ 56 ]. These position changes are normally related to a change in the distance between crystalline planes (d-spacing).…”
Section: Resultsmentioning
confidence: 99%
“…[ 55 ]. Apart from the difference in intensity of the peaks, some authors have reported a modification of the position of the main planes of BioHDPE when different substances are added to the polymer matrix [ 56 ]. These position changes are normally related to a change in the distance between crystalline planes (d-spacing).…”
Section: Resultsmentioning
confidence: 99%
“…The hybridization of biochar with wool considerably enhances the flexural strength and modulus compared to biocharreinforced polypropylene [11]. After hybridizing hair and coir fiber, Srivastava and Sinha obtained superior mechanical properties [12]. Rajkumar et al found that the hybridization of wool and silk possessed better mechanical properties [13].…”
Section: Introductionmentioning
confidence: 99%